The world according to Bob : the further adventures of one man and his street-wise cat - Bowen, James, 1979- author (New York : Thomas Dunne Books, St. Martin's Press, 2013)
The nightwatchman -- New tricks -- The Bobmobile -- The odd couple -- The ghost on the stairs -- The garbage inspector -- Cat on a Hoxton roof -- None so blind -- Bob's big night out -- Tales of two cities -- Two cool cats -- The joy of Bob -- Public enemy no. 1 -- Pride and prejudice -- The one that saves me -- Doctor Bob -- Basic instincts -- Waiting for Bob -- Epilogue: Always.